CHILD AND VIRTUAL READING: ANALYSIS OF ONLINE FRENCH CHILDREN’S BOOKS - JANKEVIČIŪTĖ, LAURA (Knygotyra, 2010)
New technologies are changing every arena of human experience and stimulate profound cultural transformations. A digital culture is developing. The arrival of new cultural forms is shaping the socialization processes, values and beliefs of young people and influences their decisions in many areas such as education or leisure and life in general. The aim of the article is to show how new technologies influence the culture of the young generation and change their attitude to traditional reading. The article offers an analysis of six online French children’s books and shows their principal characteristics. The publishing of children’s books online is an experimental field developed by independent writers and illustrators. The article presents the posture of traditional book publishers and the initiatives of the public sector in supporting the creative cultural projects such as online books. The article may be useful not only for academic society, but also for different groups of its cultured members.